The Fixed Points of Mobius Transformation - Pallavi Pawar, Vishwajeet S. Goswami (Mathematical Statistician and Engineering Applications, 2023)
In Complex Examination, a Bilinear Change of complex plane is a target limit of one complex variable z. Numerically, a Bilinear Change can be gotten by performing from plane to unit two-circle, turning and moving the circle to another space besides, bearing in space and performing stereographic projection to the plane.